JUNIOR HIGH SCHOOL TEACHERS' PERCEPTION OF TEACHER PROFESSIONAL DEVELOPMENT - Rizki Merdekawati, - (2018)
This research was conducted to investigate the teachers' perceptions of Teacher Professional Development (TPD) and their perceptions of Subject Teacher Forum (Musyawarah Guru Mata Pelajaran/ MGMP) as one of TPD programs in particular. This study employed descriptive qualitative method and involved eighteen junior high school teachers in Kabupaten Pelalawan-Riau as participants. Using CERI's (1998) in Yates (2007) principles of effective TPD, this study gathered the data through anonymous filled in questionnaire to investigate teachers' perceptions of TPD. Katz (2001) category of learning was used to reveal their perceptions of MGMP and the interview was conducted to collect the data. The result revealed that in general, teachers have positive perception of TPD regardingthe benefits gained from their participation in TPD. Teachers learned a lot from the activities and they found TPD gave positive influences for their professional learning and development. It revealed that teachers also have positive perceptions of MGMP regarding the changes on their professional competence as a result of their learning experiences in MGMP. However, despite their positive perceptions, some teachers also showed their dissatisfaction both on TPD and on MGMP in particular. They found the opportunities for participating in TPD programs were unequally distributed among teachers. Besides, they found that the activities in MGMP were not carried out as expected. Policy implications drawn for these findings were addressed to the government or the professional development providers. There should be wider chance given for all subject teachers to participate in various TPD programs. Besides, MGMP and other TPD programs should more seriously engage teachers' professional learning.